Effect of demographic factors on student teachers' achievement in the subject educational statistics (a study based on the pgde programme of the university of jaffna) - Piratheeban, K.; Rasanayakam, J.; Nithlavarnan, A. (University of Jaffna, 2022)
Purpose:The purpose of this study is to investigate the effect of demographic factors on the learning achievement of Educational Statistics of the student teachers. Methodology:Eighty-two participants were selected through purposive sampling from the students of the Post Graduate Diploma in Education (PGDE) - Full-Time course of the University of Jaffna, Sri Lanka. This study employed a cross-sectional survey design. The normality was checked by Sapiro- Wilk's test, and parametric test: independent sample t-test was used to examine whether there is any significant difference. Findings: The results of the study showed, that among these demographic factors only the nature of the Degree and the subject they teach are statistically significant in affecting the achievement of Educational Statistics. Although other demographic factors showed little differences, they were not significant. Research limitation:This study was confined to the student teachers of the PGDE-Full Time course of the University of Jaffna. And among the factors that affect learning achievement, only demographic factorshave been taken into account for this study. Implications: Knowledge of Educational Statistics is deemed an essential requirement for the teachers in the present Education scenario. To carry out research and remedial teaching-learning activities, basic knowledge of educational statistics is necessary. Therefore, basic statistical knowledge should be developed for all teachers during the service period. Thus, it has been included as a core subject in most of the teacher education courses. Based on the results of the above study the following recommendation is put forward to improve their knowledge in the subject of educational Statistics and to develop the skills to use it in the educational context in their career cycle. Teacher professional development institutions should introduce basic Mathematics and Science as a core course unit in their curriculum.
Keywords: Academic achievement; Demographic factors; Educational statistics; Student teachers